KURIKULUM MERDEKA BELAJAR PADA PEMBELAJARAN PENDIDIKAN AGAMA ISLAM - RAHMATIKA, ZAHRA; SUSANTI, AGUS; SUSILAWATI, BETI; ARAFAH, ABDUL LATIEF ARUNG; HARTIWI, JUNI (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2024)
This research departs from the phenomenon of the independent learning policy which has just been promoted by the Ministry of Education. Educational policy is a decision made by the government in the field of education as a response to educational problems that occur in society. Problems that often occur in learning are generally related to conventional learning patterns used by teachers. This pattern is enough to make students feel bored easily. Improving the quality of education will not have a significant effect without quality teachers. Therefore, it is important to implement learning in Islamic Religious Education (PAI) subjects by Islamic religious education teachers based on good concepts, in this case as developing innovation so that the expected learning objectives can be achieved. This research was conducted to determine the implementation of the Independent Learning Curriculum in Islamic Religious Education learning. This research uses a qualitative research approach. The population and sample in this study were PAI teachers. Data collection techniques were carried out by means of observation, interviews and documentation. To test the validity of the data, researchers used triangulation techniques, namely, source triangulation, technique triangulation and time triangulation. The results of this research show that the implementation of the independent learning curriculum in Islamic Religious Education learning has been carried out well. In the implementation process, it is known that there are efforts to plan, implement and evaluate schools in responding to and implementing the implementation of the Merdeka Belajar curriculum. In implementing the independent learning curriculum, there is an obstacle factor, namely the lack of understanding by teachers and students regarding what the independent learning curriculum is. ABSTRAKPenelitian ini berangkat dari fenomena kebijakan merdeka belajar yang baru digaungkan oleh Kementerian Pendidikan. Kebijakan pendidikan merupakan sebuah keputusan yang dibuat oleh pemerintah dalam bidang pendidikan sebagai respon dari masalah-masalah pendidikan yang terjadi di masyarakat. Masalah yang sering terjadi dalam pembelajaran umumnya berkaitan dengan pola pembelajaran konvensional yang digunakan oleh guru. Pola tersebut cukup membuat siswa mudah merasa bosan. Meningkatkan mutu pendidikan tidak akan berpengaruh secara signifikan tanpa guru yang berkualitas. Oleh karena itu pentingnya implementasi pembelajaran pada mata pelajaran PAI (Pendidikan Agama Islam) oleh guru pendidikan agama islam didasari dengan konsep yang baik, dalam hal ini sebagai pengembangan inovasi sehingga bisa tercapainya tujuan pembelajaran yang diharapkan. Penelitian ini dilakukan untuk mengetahui implementasi Kurikulum Merdeka Belajar pada pembelajaran Pendidikan Agama Islam. Penelitian ini menggunakan pendekatan penelitian kualitatif. Populasi dan sampel dalam penelitian ini adalah guru PAI. Teknik pengumpulan data dilakukan dengan cara observasi, wawancara dan dokumentasi. Untuk menguji keabsahan data, peneliti menggunakan teknik triangulasi yaitu, triangulasi sumber, triangulasi teknik dan triangulasi waktu. Hasil penelitian ini didapat implementasi kurikulum merdeka belajar pada pembelajaran Pendidikan Agama Islam sudah dijalankan dengan baik. Dalam proses implementasinya diketahui bahwa, terdapat upaya perencanaan, pelaksanaan dan evaluasi sekolah dalam menyikapi dan melaksanakan implementasi kurikulum Merdeka Belajar. Dalam implementasi kurikulum merdeka belajar terdapat faktor kendala yaitu kurangnya pemahaman guru dan siswa terkait apa itu kurikulum merdeka belajar.